Study on permeability law of water-based polymer drilling fluid containing CaCl2 in wellbore formation - Tianle Liu; Qi Quan; Guosheng Jiang; Shaojun Zheng; Lixia Li; Yinfei Yu (地质科技通报, 2021)
The use of microbially induced carbonate precipitation (MICP) technology to improve the cementation quality of oil and gas well cementing has attracted more and more attention in recent years. At present, cementing slurry technology containing ore-forming microorganisms has been realized for shallow oil and gas wells of 3, 000 meters. In order to make the ore-forming microorganisms in the cement slurry filtrate effectively play the role of MICP at the two interfaces to improve the quality of the two-interface cementation, it is necessary to use the drilling fluid to carry the CaCl2 in the drilling process to pre-inject a certain amount of CaCl2 into the wellbore formation. Therefore, it is necessary to study the penetration law of CaCl2-containing drilling fluid in the wellbore formation, so as to reasonably control the CaCl2 injection volume and drilling cost. Based on this, this paper takes the commonly used environmentally friendly water-based polymer drilling fluid as the basic carrier, comprehensively considers the dynamic formation mechanism of mud cake at the well wall, the variation law of physical properties of the surrounding formation and the water-based polymer drilling with CaCl2. The factors such as liquid rheology and the combination of theoretical calculation and simulation experiment were used to establish a quantitative prediction model for the permeation and permeation distance of the drilling fluid containing CaCl2 water-based polymer in the wellbore formation. The calculation results of the prediction model are consistent with the simulation test results, and have good reliability, which helps to provide the oretical support for drilling production enterprises to rationally optimize drilling fluid and cement slurry construction technology.